1996
DOI: 10.1101/gad.10.24.3094
|View full text |Cite
|
Sign up to set email alerts
|

Est1 has the properties of a single-stranded telomere end-binding protein.

Abstract: In Saccharomyces cerevisiae, deletion of the EST1 gene results in phenotypes identical to those displayed by a deletion of a known component of telomerase (the yeast telomerase RNA), arguing that EST1 is also critical for telomerase function. In this study, we show that the Estl protein binds to yeast G-rich telomeric oligonucleotides in vitro. Binding is specific for single-stranded substrates and requires a free 3' terminus, consistent with the properties expected for a protein bound to the 3' single-strande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
165
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(178 citation statements)
references
References 58 publications
10
165
0
3
Order By: Relevance
“…EST2 and TLC1 encode the reverse transcriptase catalytic protein subunit and the templating RNA, respectively 9,11,12 . In addition, the protein encoded by EST1 is associated with the RNA component of telomerase, TLC1 (refs [13][14][15][16]. Other accessory factors, such as Cdc13, are required for the in vivo action of telomerase.…”
mentioning
confidence: 99%
“…EST2 and TLC1 encode the reverse transcriptase catalytic protein subunit and the templating RNA, respectively 9,11,12 . In addition, the protein encoded by EST1 is associated with the RNA component of telomerase, TLC1 (refs [13][14][15][16]. Other accessory factors, such as Cdc13, are required for the in vivo action of telomerase.…”
mentioning
confidence: 99%
“…1). The variation in RNA affinity relative to a prior report likely reflects the use of different RNA probes (9). The Est1 RNA binding was dependent upon the bulged-stem loop structure, as a disrupted-stem RNA displayed no apparent interaction and a bulge-delete RNA had a decreased affinity (K d Ϸ300 nM).…”
Section: Est1mentioning
confidence: 80%
“…The initial Est1 biochemical characterization demonstrated that the protein preferentially binds DNAs with 3Ј single-stranded G-rich sequence (9). We wished to extend these observations by delineating the DNA length requirements for Est1 binding.…”
Section: Est1mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Cdc13p, several proteins with single-stranded telomeric DNA-binding activities have been identified in yeast [16][17][18][19]. Est1p is a telomerase-associated protein that mediates the binding of telomerase to telomeres [13].…”
Section: Introductionmentioning
confidence: 99%